Draft Eighth Five - Year Plan, 1990-95 and Annual Plan, 1991-92 Volume II Government of Bihar - Planning Commission (Planning Commission, 1990)
The population of the State is not only the second biggest after Uttar Pradesh in the country is also rising at an increasing rate. the decadal rate of growth of population was 10.27 per cent in the decade 1941—51. It rose to 19.77 per cent in 1951-61, 21.30 per cent in 1961-71 and to 24.06 per cent in the decade 1971— 81. If this rate of growth of population continues, for which there are all the indications, the population may reach the level of 86.7 millions and 95 millions on 1st March, 1991 and 1995 respectively.
Planning Department, Government of Bihar